Effect of magnetic declination on refractive index and wave polarization coefficients of electromagnetic waves in mid-latitude ionosphere - Aydogdu, Mehmet; Ozcan, Osman (My University, 1996)
General forms of conductivity tensor, refractive index and wave polarization coefficients for ionospheric plasma are developed by including the magnetic declination and dip angle. Calculations show that polarization coefficients become complex numbers when magnetic declination is included, while they are pure imaginary in the absence of declination. The declinational effect on the real parts of the polarization coefficients is more pronounced around plasma frequency than at other frequencies. However, the imaginary parts and refractive index are not affected at the plasma frequency.